Legalization of Marijuana in the Medical Sector: A Criminal Law Perspective - Amalia, Mia; Sandi, Chintia; Mulyana, Aji (Indonesian Journal of Law and Justice, 2024)
Marijuana is a plant that is illegal in Indonesia today. This is regulated in law 35 of 2009 concerning narcotics.2009 on narcotics. Although the use of marijuana is still reaping the pros and cons, one of the followingorganization LGN (lingkat ganja nusantara) is fighting for legalization and expanding to educate the public.educate the public. Marijuana, which is viewed negatively by society, in fact provides many benefits for the medical sector where it is used as a drug.benefits for the medical sector where it is used as an alternative treatment with the doctor's compliance. The conclusion of this study is that the government continues to prohibit the legalization and use of marijuana for medical purposes with the aim of protecting all Indonesian people from new problems that are at risk of arising and to strengthen the government's narrative about marijuana policy for medical purposes requires empirical testing by involving academics to strengthen government policy arguments and clinical trials.